The Sufficient Immunoregulatory Effect of Autologous Bone Marrow-Derived Mesenchymal Stem Cell Transplantation on Regulatory T Cells in Patients with Refractory Rheumatoid Arthritis - Mohsen Ghoryani; Zhaleh Shariati-Sarabi; Jalil Tavakkol-Afshari; Mojgan Mohammadi (Journal of Immunology Research)
Rheumatoid arthritis (RA) is an advanced autoimmune disease described by joint involvement. The special properties of mesenchymal stem cells (MSCs) introduced them as a potential therapeutic candidate for RA. In this study, a single dose of autologous MSCs isolated from bone marrow (autologous BM-MSCs, 1×106 per kg) was injected intravenously into 13 patients suffering from refractory RA who were followed up within 12 months after the intervention to evaluate immunological elements. Our results showed that the gene expression of forkhead box P3 (FOXP3) in peripheral blood mononuclear cells (PBMCs) considerably increased at month 12. We found a substantial increasing trend in the culture supernatant levels of IL-10 and transforming growth factor-beta 1 (TGF-β1) in PBMCs from the beginning of the intervention up to the end. Our data may reflect the sufficient immunoregulatory effect of autologous BM-MSCs on regulatory T cells in patients suffering from refractory RA.